Children's literature and body awareness: an eight-stage reading between picture books and somatics - Marcella Terrusi (University of Bologna, 2023)
The article proposes looking at children's literature, particularly the form of the picture book, as an educational resource for producing body awareness in school. Eight reading steps for as many bodily actions aimed at naming the body, activating it, getting to know it and moving it in space, on and off the pages; between grounding, listening, breathing, playing and moving, the rediscovery of gestures and anatomical truths invites to deepen self-knowledge as a preliminary act to the encounter and relationship with the other and with the environment. The picture books by their specificities of short form and cross-over, offer, even in non-fiction production, the possibility of bringing attention back to the body dimension within the school and educational debate, where it lives today in a state of malaise and oblivion. Meaningful conversations, explorations and relationships flow from the pages of the albums: research on language as a tool that gives dignity and value to each person, and encounters with the artistic representation of the world as an infinite mirror of its multiplicity and variety, constitute valuable opportunities for an education that is aware of the wholeness of learners and teachers and the integrated, erotic and embodied dimension of their relationship.